Detecting Financial Reporting Fraud through the Fraud Pentagon Approach - Siti Nor Halipah; Anisa Kusumawardani (UNIVERSITAS DHARMAWANGSA, 2026)
This study analyzes the influence of fraud pentagon elements on financial statement fraud in basic materials companies listed on the Indonesia Stock Exchange. Independent variables include financial targets, ineffective monitoring, auditor switching, director turnover, CEO photo count, and external pressure. Using a quantitative approach with multiple linear regression, the results show that financial targets have a significant positive effect on financial statement fraud (β = 0.295; sig = 0.001), indicating that performance pressure drives management to manipulate reports. Auditor switching has a significant negative effect (β = -0.169; sig = 0.033), suggesting it acts as a preventive mechanism that strengthens independence and professional skepticism. Meanwhile, ineffective monitoring (β = 0.030; sig = 0.702), director turnover (β = 0.107; sig = 0.183), CEO photo count (β = -0.068; sig = 0.390), and external pressure (β = -0.123; sig = 0.157) show no significant impact. These findings highlight that in the basic materials sector, financial targets are the dominant driver of fraudulent reporting, while other governance mechanisms such as external monitoring, board composition, and CEO narcissism fail to consistently explain fraud occurrence. This study contributes theoretically to the development of fraud pentagon theory and provides practical implications for regulators, auditors, and practitioners in designing more effective fraud prevention strategies.